Risk assessment for hepatitis E virus infection from domestic pigs introduced into an experimental animal facility in a medical school - OGAWA, Hirohito; HIRAYAMA, Haruko; TANAKA, Satsuki; YATA, Norio; NAMBA, Hikaru; YAMASHITA, Nobuko; YONEMITSU, Kenzo; MAEDA, Ken; MOMINOKI, Katsumi; YAMADA, Masao (Journal of Veterinary Medical Science, 2019)
Hepatitis E virus (HEV) is known to cause zoonotic infections from pigs, wild boars and deer. Domestic pigs have been used as an experimental animal model in medical research and training; however, the risks of HEV infection from pigs during animal experiments are largely unknown. Here, we retrospectively investigated the seroprevalence and detection rates of viral RNA in 73 domestic pigs (average 34.5 kg) introduced into an animal experimental facility in a medical school during 2012–2016. We detected anti-HEV immunoglobulin G antibodies in 24 of 73 plasma samples (32.9%), though none of the samples were positive for viral RNA. Plasma samples of 18 pigs were sequentially monitored and were classified into four patterns: sustained positive (5 pigs), sustained negative (5 pigs), conversion to positive (6 pigs) and conversion to negative (2 pigs). HEV genomes were detected in 2 of 4 liver samples from pigs that were transported from the same farm during 2016–2017. Two viral sequences of the overlapping open reading frame (ORF) 2/3 region (97 bp) were identical and phylogenetically fell into genotype 3. A 459-bp length of the ORF2 region of an amplified fragment from a pig transported in 2017 was clustered with the wbJYG1 isolate (subgenotype 3b) with 91.5% (420/459 bp) nucleotide identity. Based on our results, we suggest that domestic pigs introduced into animal facilities carry a potential risk of HEV infection to researchers, trainees and facility staff. Continuous surveillance and precautions are important to prevent HEV infection in animal facilities.